2020
DOI: 10.1371/journal.ppat.1008467
|View full text |Cite
|
Sign up to set email alerts
|

Novel partiti-like viruses are conditional mutualistic symbionts in their normal lepidopteran host, African armyworm, but parasitic in a novel host, Fall armyworm

Abstract: Recent advances in next generation sequencing (NGS) (e.g. metagenomic and transcriptomic sequencing) have facilitated the discovery of a large number of new insect viruses, but the characterization of these viruses is still in its infancy. Here, we report the discovery, using RNA-seq, of three new partiti-like viruses from African armyworm, Spodoptera exempta (Lepidoptera: Noctuidae), which are all vertically-transmitted transovarially from mother to offspring with high efficiency. Experimental studies show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(112 citation statements)
references
References 78 publications
(151 reference statements)
5
99
1
Order By: Relevance
“…exempta results in the initiation of larval outbreaks, which can cause severe damage to rangeland grasses and crops, including maize, millet, rice, wheat, among others (Parker and Gatehouse 1985a , 1985b ; Xu et al. 2020 ). To date, S .…”
mentioning
confidence: 99%
“…exempta results in the initiation of larval outbreaks, which can cause severe damage to rangeland grasses and crops, including maize, millet, rice, wheat, among others (Parker and Gatehouse 1985a , 1985b ; Xu et al. 2020 ). To date, S .…”
mentioning
confidence: 99%
“…For individuals reared on L. albifrons , survival was enhanced when infected with the virus, regardless of immunocompetence as measured by PO. This curious result requires further investigation, but it is noteworthy that at least one other study found higher survival frequency in individuals infected with a densovirus ( Xu et al 2014 ), indicating that under certain conditions not all viruses are pathogenic ( Suttle 2013 , Roossinck 2015 , Xu et al 2020 ). We suggest that future studies delve into differences in host plant traits that may contribute to different outcomes of pathogen infection.…”
Section: Resultsmentioning
confidence: 99%
“…Given the apparent lack of horizontal transmission of partitiviruses, it is not clear how deltapartitiviruses found their plant hosts, although there is a close relationship between plant and fungal partitiviruses (Roossinck, 2019). In addition to infecting plants, fungi and protozoa, partitivirus-like sequences have now been found to be common in wild populations of arthropods (Pettersson et al, 2019) where they are also vertically transmitted (Cross et al, 2020;Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%